Clinical Profile of Hyper-IgE Syndrome in India - Saikia, Biman; Rawat, Amit; Minz, Ranjana W.; Suri, Deepti; Pandiarajan, Vignesh; Jindal, Ankur; Sahu, Smrity; Karim, Adil; Desai, Mukesh; Taur, Prasad D.; Pandrowala, Ambreen; Gowri, Vijaya; et al. (Frontiers in Immunology, 2021)
Introduction: Hyper-IgE Syndrome (HIES) is a rare inborn error of immunity (IEI) characterized by a constellation of symptoms related to susceptibility to Staphylococcal skin and pulmonary infections, eczema, raised serum IgE (>2000 IU/ml), craniofacial anomalies, and recurrent bone fractures. Data on HIES from the Indian subcontinent is scarce and restricted to small case series and case reports. This is the first compilation of national data on HIES. Materials and methods: A total 103 cases clinically diagnosed and treated as HIES were analyzed from 9 centers. Cases with clinical and/or molecular diagnosis of DOCK8 deficiency were not included. Patients were divided into two groups: group I for whom a heterozygous rare variant of STAT3 was identified, and group II, with clinical features similar to those of AD STAT3 deficiency, but without any genetic diagnosis. Results: Genetic diagnosis was available in 27 patients (26.2%) and all harbored rare variants in the STAT3 gene. Majority of these STAT3 HIES patients presented with recurrent skin abscesses (77.7%) or pneumonia (62.9%) or both (59.2%). Other features included eczema (37%), candidiasis (55.5%), facial dysmorphism (55.5%), recurrent fractures (11.1%), and retained primary teeth (7.4%). Mycobacterial infections were seen in a significant 18.5%. Mortality was seen in 3 subjects (11.1%). A similar trend in the clinical presentation was observed when all the 103 patients were analyzed together. 20% of patients without a rare variant in the STAT3 gene had an NIH score of ≥40, whereas, 51.9% of STAT3 HIES subjects had scores below the cut off of ≥40. TH17 cell numbers were low in 10/11 (90.9%) STAT3 HIES tested. Rare variants observed were 8 in exon 21; 8 in exon 13; 3 in exon 10; 2 in exon 15, and one each in exon 6, 16, 17, 19, 22 and splice site downstream of exon 12. Seven variants were novel and included F174S, N567D, L404Sfs*8, G419=, M329K, T714I, R518X and a splice site variant downstream of exon 12. Conclusions: The report includes 7 novel STAT3 variants, including a rare linker domain nonsense variant and a CC domain variant. Mycobacterial diseases were more frequent, compared to western literature.